2000
DOI: 10.3758/bf03205551
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pattern and spectral complexity as stimulus parameters for eliciting a cardiacorienting reflex inhuman fetuses

Abstract: The purpose of this study was to determine whether temporal pattern and/or spectral complexity were important stimulus parameters for eliciting a cardiac orienting reflex (OR) in low-risk human fetuses. Each of28 term fetuses was exposed to four sounds formed from the four different combinations of temporal pattern (pulsed, continuous) and spectral complexity (sine wave, /3/). The fetal cardiac electrical signal was captured transabdominally at a rate of 1024Hz, and fetal R-waves were extracted by using adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This possibility has been broached previously based on the rapidity of onset of a fetal response to a maternal event (DiPietro et al, 2003;Novak, 2004). FHR responses have been observed within seconds of disruptions of the maternal environment in investigations of sensory capacities, including maternal postural changes (Lecaneut et al, 2002) and auditory stimuli (Groome et al, 2000) and it is clear that sounds generated by maternal vasculature and the digestive tract are prominent in the uterine auditory environment (Querleu, Renard, Boutteville, & Crepin, 1989). It is possible that induced maternal relaxation may generate a biphasic response that includes a rapid sensory-mediated component as well as a secondary response mediated by neurohormonal or vasodilatory processes that extends beyond the confines of this study's protocol.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been broached previously based on the rapidity of onset of a fetal response to a maternal event (DiPietro et al, 2003;Novak, 2004). FHR responses have been observed within seconds of disruptions of the maternal environment in investigations of sensory capacities, including maternal postural changes (Lecaneut et al, 2002) and auditory stimuli (Groome et al, 2000) and it is clear that sounds generated by maternal vasculature and the digestive tract are prominent in the uterine auditory environment (Querleu, Renard, Boutteville, & Crepin, 1989). It is possible that induced maternal relaxation may generate a biphasic response that includes a rapid sensory-mediated component as well as a secondary response mediated by neurohormonal or vasodilatory processes that extends beyond the confines of this study's protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Audiotactile interactions in rhythm perception and sensorimotor synchronization Some authors have observed that, whereas the spatial properties of the objects-typically related to visual functions-develop after birth, some temporal properties, such as synchrony, tempo, and rhythm, are experienced during prenatal life, through vestibular, tactile, and auditory stimulation (e.g., Groome et al, 2000;Woodward & Guidozzi, 1992). The different line of development of the sensory modalities would contribute in generating specific "salience hierarchies" for object/event properties, with the processing of auditory-somatosensory synchrony-such as the one elicited by the maternal heartbeat-being one of the first sensory experiences we humans are exposed to (Lickliter & Bahrick, 2000).…”
Section: Audiotactile Interactions Based On Frequency Similaritymentioning
confidence: 99%
“…Heart rate decreased in response to auditory stimulation, with a greater decrease occurring during active sleep than quiet sleep. A similar study found that pulsed sounds elicited a greater heart rate decrease than did continuous sounds, regardless of the spectral complexity (Groome et al, 2000).…”
Section: Discussionmentioning
confidence: 76%